EARLY CENTRAL BORNEO PROJECT: ARCHAEOLOGICAL INVESTIGATIONS IN PA' LUNGAN, KELABIT HIGHLANDS (2013-2015) - Lindsay, Lloyd-Smith; Nicholas, Gani; Mohammed Sherman, Sauffi William; Jo, Appleby; Stephen, Litah; Stephen, Murphy; Borbála, Nyiri; Walter, Paran; Nancy, White (SARAWAK MUSEUM DEPARTMENT, 2017)
This is a summary report on three field seasons (2013, 2014, 2015) of the Early Central Borneo Project investigating the prehistory of the Kelabit Highlands, Sarawak (Fig. 1). This work builds upon the results of previous anthropological and archaeological research in the region, particularly Sarah Hitcher's comprehensive anthropological survey of cultural sites (2009), and the work of the inter-disciplinary work of the Cultured Rainforest Project (CRF) (2007-2010) which investigated the socio-ecological history of the Central Kelapang Valley in the southern Kelabit Highlands (Barker et al. 2007, 2008; Lloyd-Smith et al. 2010, 2012). The Kelabit Highlands and adjacent headwaters of central Borneo have long been renowned for the numerous stone and earthwork monuments, and surveys on both sides of the central spinal watershed of Borneo (which today forms the international border between Sarawak Malaysia and Kalimantan Indonesia) have demonstrated the wide extent and diversity of monument types. Although there had been some excavation of a few megalithic sites on the Sarawak side of the border in the 1960s by Sarawak Museum, and in the 1990s of a limited number of settlement sites on the Kalimantan side of the border by an Indonesian-led international social-science research team (Arifin and Sellato 2003), it was not until the 2007-2010 CRF project that the first systematic archaeological excavations of multiple site types was carried out with the aim of producing a secure chronological framework for the highland region.